2020
DOI: 10.1016/j.omtn.2019.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of GAS5 Inhibits Atherosclerosis Progression via Reducing EZH2-Mediated ABCA1 Transcription in ApoE−/− Mice

Abstract: Atherosclerosis is a disorder occurring in the large arteries and the primary cause of heart diseases. Accumulating evidence has implicated long non-coding RNAs (lncRNAs) in atherosclerosis. This study aims to clarify the potential effects of lncRNA growth arrest-specific 5 (GAS5) on cholesterol reverse-transport and intracellular lipid accumulation in atherosclerosis. GAS5 was mainly localized in the nucleus and highly expressed in the human monocytic leukemia cell line (THP-1) macrophage-derived foam cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 41 publications
4
71
0
Order By: Relevance
“…Of the mechanisms that have been described, pathway included ABCA1/ABCG1 was widely studied. [16][17][18][19] As far as we know, cholesterol efflux transport relies on some specific proteins, such as ABCA1 and ABCG1, which has been regarded as gatekeeper for mediating tissue cholesterol. 20 ABCA1 and ABCG1 present additional activities during enhancing process of reverse cholesterol transport in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Of the mechanisms that have been described, pathway included ABCA1/ABCG1 was widely studied. [16][17][18][19] As far as we know, cholesterol efflux transport relies on some specific proteins, such as ABCA1 and ABCG1, which has been regarded as gatekeeper for mediating tissue cholesterol. 20 ABCA1 and ABCG1 present additional activities during enhancing process of reverse cholesterol transport in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…ApoE-/-mice with overexpression of GAS5 or EZH2 showed increased total cholesterol, free cholesterol, cholesterol ester, low-density lipoprotein levels, aortic plaque, and lipid accumulation, accompanied by reduced HDL levels and cholesterol outflow. These data suggest GAS5 as a promising target to restore cholesterol homeostasis and inhibit atherosclerotic plaque formation in patients [86].…”
Section: Reverse Cholesterol Transport -Abca1 and Abcg1 Regulationmentioning
confidence: 84%
“…Macrophage-expressed lncRNAs can also have detrimental effects on foam cell formation through the inhibition of ABCA1. In the study by Meng et al [86], the lncRNA growth arrest-specific 5 (GAS5) was highly expressed in the THP-1 macrophage-derived foam cells and localized primarily to the nucleus. The overexpression of GAS5 facilitated lipid accumulation and foam cell formation.…”
Section: Reverse Cholesterol Transport -Abca1 and Abcg1 Regulationmentioning
confidence: 99%
“…A recent study showed that lncRNA GAS5 was mainly localized in the nucleus and highly expressed in THP-1 macrophage-derived foam cells in coronary heart disease. The knockdown of GAS5 increased cholesterol efflux and inhibited intracellular lipid accumulation in THP-1 macrophage-derived foam cells and homozygous apolipoprotein E (ApoE) knockout mice by reducing the EZH2-mediated transcriptional inhibition of ABCA1 by histone methylation (66). The overexpression of RP-833A20.1 in THP-1 macrophages may also decrease cholesterol efflux.…”
Section: Role Of Lncrnas In Lipid Effluxmentioning
confidence: 99%
“…Lipid disorders cause lipoprotein accumulation within middle and large artery walls, thus triggering atherosclerosis (155). Several lncRNAs are involved in lipid metabolism-related disorders through the regulation of lipid synthesis, reverse cholesterol transport, and bile acid excretion (63,66). The formation of macrophage foam cells, which play central roles in the initiation and progression of atherosclerotic plaques, has been shown to be closely related to DYNLRB2-2, MeXis, and RP5-833A20.1 (63,64,67).…”
Section: Atherosclerosismentioning
confidence: 99%